Spread of Veronica filiformis (Scrophulariaceae) in the Sudetes - Pielech, Remigiusz; Zając, Krzysztof; Malicki, Marek (Biodiversity: Research and Conservation, 2013)
Veronica filiformis is an alien plant species widely distributed, across Central and Western Europe. The first observation of the species in the Sudetes was reported in 1942. Until 2000, only a few scattered sites were known in south-western Poland. During the last decade, V.filiformis was observed more frequently in many ranges of the Sudetes. In 2007, field works intended to discover new sites of the species were conducted as well as a critical revision of herbarium specimens stored in WRSL was performed. The number of known localities totals 37. Almost 65% of them were discovered during the last decade. The data are now summarized to bring up to date the known distribution and invasion scale of V. filiformis in the Polish part of the Sudetes.